2007
DOI: 10.1002/jcb.21599
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA from Salvia miltiorrhiza BUNGE inhibits human aortic smooth muscle cell migration and MMP‐9 activity through AKT signaling pathway

Abstract: Smooth muscle cell (SMC) migration plays an important role in normal angiogenesis and is relevant to disease-related vascular remodeling in conditions such as brain arteriovenous malformations, pulmonary hypertension, arteriosclerosis, and restenosis after angioplasty. In this present study, we showed that tanshinone IIA, the major lipid-soluble pharmacological constituent of Salvia miltiorrhiza BUNGE, inhibits human aortic smooth muscle cell (HASMC) migration and MMP-9 activity. Tanshinone IIA significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 47 publications
(56 reference statements)
2
71
0
Order By: Relevance
“…Numerous cell signaling pathways are critical in the regulation of MMPs (4,17,23,24). For example, the AKT signaling pathway is associated with the expression of MMP-2/-9 in healthy and cancerous tissues (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous cell signaling pathways are critical in the regulation of MMPs (4,17,23,24). For example, the AKT signaling pathway is associated with the expression of MMP-2/-9 in healthy and cancerous tissues (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the AKT signaling pathway is associated with the expression of MMP-2/-9 in healthy and cancerous tissues (24,25). Furthermore, the antitumor effects of baicalein treatment are associated with the AKT signaling pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has shown that tanshinone IIA increases coronary blood flow and protects the heart against cardiac injury [17] . On the basis of the cardioprotective action of tanshinone IIA, we investigated the hypothesis that tanshinone IIA may prevent the death of cardiomyocytes.…”
Section: Role Of Akt In the Protective Effect Of Tanshinone Iia On Anmentioning
confidence: 99%
“…The MAPK pathway (JNK, p38 and ERK) is one of the molecular mechanisms to regulate cancer cell activity. Phospho-p38 can induce apoptosis and phospho-ERK can inhibit apoptosis (27)(28)(29). Our results showed that Tan-IIA increased the protein expression levels of p-JNK (especially after 1 h) and p-p38 (especially after 6 h).…”
Section: The Effects Of Tan-iia On the Protein Expression Of Bax Bclmentioning
confidence: 56%